Prognostic significance of CXCL12, CXCR4, and CXCR7 in patients with breast cancer - Wu, Wei (Int J Clin Exp Pathol, 2015)
Background: The chemokine CXCL12 and its receptors CXCR4 and CXCR7 play important roles in cancer invasion and metastasis. This study investigated the mRNA expressions of CXCL12, CXCR4, and CXCR7 to illustrate the role of these biomarkers in breast cancer metastasis and prognosis. Methods: The mRNA expressions of CXCL12, CXCR4, and CXCR7 in 115 primary breast cancer and regional lymph node specimens were detected by quantitative reverse-transcription polymerase chain reaction. Survival time was analyzed by Kaplan-Meier survival curves using log-rank test. Univariable and multivariable Cox regression analyses were performed to assess independent prognostic factors for survival. Results: The expression levels of CXCR4 and CXCR7 in breast cancer tissues were significantly higher than that in adjacent normal tissues (P=0.022 and P<0.001, respectively), while the expression level of CXCL12 in breast cancer tissues did not differ from that in adjacent normal tissues (P=0.156). Furthermore, CXCL12 exhibited significant differences in expression between primary tumor and lymph node metastasis tumor (P=0.039). CXCR4 and CXCR7 expressions in metastasis tumor were also higher, although no significant difference was observed (P=0.067 and P=0.054, respectively). Kaplan-Meier survival analysis revealed that patients exhibiting high CXCR4 and CXCR7 expression experienced a shorter survival period compared with those with low expression. When analyzed with a Cox regression model, the expressions of CXCL12, CXCR4 and CXCR7 were independent prognostic factors for overall survival. Conclusions: The mRNA expressions of CXCL12, CXCR4, and CXCR7 play important roles in the progression and metastasis of breast cancer and may act as predictive factors significantly affecting the prognosis.